Accounting Information Systems and Financial Literacy impact on SMEs' performance - Christanty, Lany; Nugroho, Wawan Sadtyo; Nurcahyono, Nurcahyono; Maharani, Betari (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2023)
SMEs are a priority business sector in Indonesia because contribute to its economy by absorbing a large workforce. This study investigates factors SMEs can use to improve their business performance. Factors that are predictors for improving SMEs' performance are accounting information systems, quality of financial reports, financial literacy and business age. The population of this study were SMEs registered at the Magelang Cooperative and SMEs Service. The sampling method chosen was simple random sampling with 400 SMEs as respondents. Data analysis used Structural Equation Modeling-Partial Least Square (SEM-PLS) with the WarpPLS 8.0 application. The results of the study show that accounting information systems and the quality of financial reports positively affect the performance of SMEs, so optimizing these factors will create a competitive advantage. The financial literacy and business age variables do not affect the performance of SMEs, so they cannot be predictors.